Efeitos de consequências verbais culturais e de suporte sobre a seleção e manutenção de culturantes - BISPO, Gehazi Ramiris dos Santos (Universidade Federal do Pará, 2019)
Recent empirical evidence suggests a facilitating role of verbal variables on cultural selection. However, most of the data are still inconclusive or do not demonstrate the isolated effects of the direct manipulation of verbal variables, functioning as operant and cultural consequences, on the selection of culturants. In this sense, the objective of this study was to compare the differential effects of cultural and operant verbal consequences on the selection and maintenance of culturants, in the presence and absence of nonverbal cultural consequences in two laboratory microcultures using an analog of single subject ABCBCA experimental design. The results showed that the verbal operant consequences are inefficient in cultural selection once compared to the cultural consequences. When cultural, the difference in effect between verbal and non-verbal consequences is low. When cultural verbal and non-verbal consequences are combined, cultural selection is more effective.